Enhancing synergies between gender equality and biodiversity, climate, and land degradation neutrality goals: Lessons from gender-responsive nature-based approaches - Elias, Marlène; Ihalainen, Markus; Monterroso, Iliana; Gallant, Bryce; Paez Valencia, Ana Maria (2021)
Land- and nature-based approaches in the agroforestry and forestry sectors provide a unique opportunity to generate win-wins against the interrelated environmental crises of biodiversity loss, climate change, and land degradation. Harnessing synergies among these environmental goals, reflected in the Rio Conventions, critically hinges on land-use decisions, which are influenced by social dynamics – including gender. Yet, despite the linkages between gender equality and climate change, biodiversity loss, and land degradation, approaches that generate desirable feedback loops among these processes remain poorly understood and applied. This paper explores how putting gender equity at the forefront of nature-based solutions can help leverage synergies among the Rio Conventions' environmental goals. Moreover, it examines the possible risks that nature-based approaches used to advance these goals can pose to gender equality if these approaches are not responsive to gender issues. Through a social equity framework, we demonstrate that greater gains can be accrued from gender-responsive nature-based approaches that address a wider set of priorities, harness a broader set of skills to address environmental ails, enhance capacities of marginalized groups by securing their rights and access to resources, and generate more equitable incentives to garner the buy-in of an array of actors. Our examples also illustrate potential tensions between social and environmental objectives, highlighting the need to carefully consider and reconcile trade-offs while incorporating strong social safeguards.